A Constituição Federal De 1967 E O Problema Da Institucionalização Do Autoritarismo - Souza, Lucas Vieira De [UNIFESP] (2017)
Under what conditions can a political regime be considered institutionalized? What role does a Constitution play in the process and in the condition of institutionalization? In particular, what were the formative stages of the political-institutional structure of the regime that was set up from the "revolutionary" movement of March 1964 in Brazil? And what measures and arrangements did the coup-making coalition use to structure the political regime that followed the coup d'état? In this study, we sought to highlight the phases, actors, measures and institutions that are constructed by the winning coalition of 1964 until the promulgation of the Federal Constitution of 1967. First of all, the 1966-1967 constitutional process itself is uniquely unknown.1 Therefore, the central task we set ourselves was to reconstruct, thoroughly and systematically, the elaboration of the 1967 Federal Constitution: the main actors, the projects attempted , the episodes that marked the stages since the Castello Branco Government gave news of its elaboration, the alternatives put to the different participants, the tensions and also the collaborations between civil and military, between the legal opposition and the government.